KONSEKUENSI BAGI DEBITOR YANG TIDAK MENGAJUKAN RENCANA PERDAMAIAN DALAM PROSES PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Aidhya Diory Amamie Marpaung; Akhmad Budi Cahyono (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
A settlement offer in the process of suspension of debt payment obligation is in principle given to convince creditors that the debtor has the desire to settle their debts. When the debtor is in an unstable condition and feels unable to pay his debts, the law provides the debtor with the opportunity for the debt payment obligation to be suspended and provide a settlement offer for their creditors, which is regulated in Article 222 paragraph (2) of the Law No. 37 of 2004. However, in practice, it turns out some debtors do not use this opportunity to provide a settlement offer, in which case the Law No. 37 of 2004 does not explicitly regulate the legal consequences. This is the focus of this research by reviewing and discussing several jurisprudence/judge decisions with different legal considerations to see what the legal consequences are if the Debtor does not submit a settlement offer.